Electronic Effects of the Backbone on Bis(imino)pyridyliron(II)‐Catalyzed Ethylene Polymerization. Issue 45 (28th November 2018) - Guo, Lihua; Liu, Yanlan; Lian, Kunbo; Sun, Wenting; Zhu, Huaxia; Du, Qing; Liu, Zhe; Chen, Xiaoyu; Dai, Shengyu
Abstract : A series of bis(imino)pyridyl iron(II) complexes1 –5 with electron‐donating and ‐withdrawing substituents on the backbone of the ligand have been synthesized and characterized. Activated with methylaluminoxane (MAO), ethylene polymerization by these iron(II) complexes was investigated in detail, involving the electronic effect and influence of reaction conditions on catalyst activity and polymer molecular weight. The electronic perturbations exert great influence on the catalytic activity of ethylene polymerization. Complexes bearing electron‐withdrawing substituents in the 4‐position of the pyridine ring showed the better activity than analogues bearing electron‐donating substituents. However, no clear trend was observed for the dependence of polymer molecular weight on these substituents. In particular, the binuclear iron(III) complex2′ we obtained by accident displayed a similar catalytic behavior compared to its iron(II) analogue complex2 . Abstract : A series of bis(imino)pyridyl iron(II) complexes bearing a range of electron‐donating and ‐withdrawing substituents in the 4‐position of the pyridine ring have been synthesized and characterized. The aim is to systematically investigate the backbone electronic effects on their catalytic properties in ethylene polymerization.